The reality of employing Instructional Technology in learning Islamic culture at the Institute of Arabic Linguistics at King Saud University from the point of view of students - Maiga, Ibrahim Abdoul- Aziz; Al Massad, Ahmed bin Zaid (Journal of Educational and Psychological Sciences, 2020)
The study aimed to uncover the reality of employing Instructional Technology in learning Islamic culture at the Institute of Arabic Linguistics at King Saud University from students` point of view. The sample of the study was composed of all members of the study society, in the Department of Language and Culture in the second semester of 2017/2018. Descriptive approach was used and questionnaire as a study tool. Among the study results: that students employ some of the Instructional Technology in learning, such as websites, and don`t employ some of them, such as social media. The teacher also employs some Instructional Technology such as smartboard and doesn`t use some of them, such as e- learning blogs. The main obstacles were the lack of appropriate training for students in the use of Instructional Technology. There were statistically significant differences between the average responses of the study subjects on the second and third axes according to the educational level variable in favor of the third level. There were no statistically significant differences between the average responses of the study members on the first axis. The researchers recommended: preparing and implementing training programs for students on how to employ modern Instructional Technology.